Pagamentos por serviços ambientais, custos de oportunidade e a transição para usos da terra alternativos:: o caso de agricultores familiares do Nordeste Paraense - Costa, Rosangela Calado da; Piketty, Marie-Gabrielle; Abramovay, Ricardo (Sustainability in Debate, 2013)
In this article, we evaluate the role that the payment for environmental services proposed by public policy Proambiente (2003-2007) might have had on the replacement of traditional land use (slash-and-burn cultivation) and the adoption of alternative land uses, able to provide higher levels of environmental services, among family farmers in the Northeast of Pará, Brazilian Amazon. For this, we simulated scenarios with estimates of opportunity costs for traditional and alternative land uses (fire-free fallow management, agroforestry, açai management, fallow vegetation enrichment and beekeeping). The results indicated that payment of Proambiente would have been insufficient to encourage the abandonment of traditional land use and could have been more promising to provide conditions for family farmers to carry out the transition to land uses capable of providing higher levels of income in the long term, such as agroforestry and açai management.